2006
DOI: 10.1029/2005ja011433
|View full text |Cite
|
Sign up to set email alerts
|

Unusual topside ionospheric density response to the November 2003 superstorm

Abstract: [1] We use observations from a variety of different ground-and space-based instruments, including ionosonde, ground-and space-based Global Positioning System (GPS) receivers, magnetometers, and solar wind data from the Advanced Composition Explorer (ACE), to examine the response of the ionospheric F2-layer height during the November 2003 superstorm. We found that the topside ionosphere responded unusually to the 20 November 2003 severe storm compared to behavior observed in a number of previous storms. While g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
57
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 26 publications
3
57
5
Order By: Relevance
“…Moreover, the height of maximum electron density exceeds 400 km and increases by 100 km compared with the quiet day over the South American area from middle to low latitudes, which might have resulted from a continuous eastward penetration electric field and storm-generated equatorward winds. Our results do not support the conclusions of Yizengaw et al (2006), who suggested that the observed positive storm over the South American sector was mainly the consequence of the changes of the bottomside ionosphere. The so-called "unusual" responses of the topside ionosphere for the November 2003 storm in Yizengaw et al (2006) are likely associated with the erroneous usage of magnetometer and incomplete data.…”
contrasting
confidence: 57%
See 4 more Smart Citations
“…Moreover, the height of maximum electron density exceeds 400 km and increases by 100 km compared with the quiet day over the South American area from middle to low latitudes, which might have resulted from a continuous eastward penetration electric field and storm-generated equatorward winds. Our results do not support the conclusions of Yizengaw et al (2006), who suggested that the observed positive storm over the South American sector was mainly the consequence of the changes of the bottomside ionosphere. The so-called "unusual" responses of the topside ionosphere for the November 2003 storm in Yizengaw et al (2006) are likely associated with the erroneous usage of magnetometer and incomplete data.…”
contrasting
confidence: 57%
“…Our results do not support the conclusions of Yizengaw et al (2006), who suggested that the observed positive storm over the South American sector was mainly the consequence of the changes of the bottomside ionosphere. The so-called "unusual" responses of the topside ionosphere for the November 2003 storm in Yizengaw et al (2006) are likely associated with the erroneous usage of magnetometer and incomplete data. …”
contrasting
confidence: 57%
See 3 more Smart Citations